Madeung Cultural Practices on Postpartum Maternal Health in Aceh - Rika, Erlia Rosita; Margawati, Ani; Andriani, Rika; Bancin, Ratnawati; Asyura, Syarifah; Makruf, Hafizul; Samsidar, Samsidar (Griya Widya: Journal of Sexual and Reproductive Health, 2025)
Background: Nagan Raya is one of the districts that still carrying out the culture of madeung for postpartum mothers.The postpartum mothers do the culture of madeung in order to get health in the future. The purpose of this study was to explore in indepth about the culture of madeung for postpartum mothers in the working area of Jeuram (Parom) Public Health Center in Nagan Raya Regency, Aceh, Indonesia. Method: This researh was a qualitative study with ethnographic approach with in-depth interviews conducted on 11 participants who were obtained by purposive sampling. Data analysis in this study was analyzed using content analysis.  The data in this study uses data triangulation. Result: The result of the research showed that the culture of madeung for example dietary restrictions,  bareut pruet (abdominal belt), using warm stone (toet bate), naite, prohibiting to go out of the house for 44 day can have a negative impact on postpartum mothers.   Implication: It is recommended that the management of Jeuram (Parom) Puskesmas develop healthpromotion not only to postpartum mothers but also to the whole community, including the oldgeneration, about the culture of madeung, particularly about restricted tocertain foods,abdominal belt, using warm stone, and fumigation which can harm the health of mothers and their babies in in the future. Novelty: The present study revealed the madeung culture for postpartum mothers in Aceh specially In the District of Nagan Raya